Comparison between the WHO and NIAAA criteria for binge drinking on drinking features and alcohol-related aftermaths: Results from a cross-sectional study among eight emergency wards in France. (1st June 2017) - Rolland, Benjamin; Chazeron, Ingrid de; Carpentier, Françoise; Moustafa, Fares; Viallon, Alain; Jacob, Xavier; Lesage, Patrick; Ragonnet, Delphine; Genty, Annick; Geneste, Julie; Poulet, Emmanuel; Dematteis, Maurice; et al.
Highlights: Compared to World Health Organization (WHO) binge drinkers, National Institute on Alcoholism and Alcohol Abuse (NIAAA) bingers were younger and were more likely males. Drinking frequencies and average levels of drinking were greater among NIAAA bingers. Features of alcohol-related aftermaths and psychiatric problems were more frequent. An overall severity gradient was found between non-bingers, WHO bingers, and NIAAA bingers. Abstract: Background: Binge drinking (BD) consists of heavy episodic alcohol use. Whereas the World Health Organization (WHO) defines BD as 60 g of alcohol or more per occasion, the National Institute on Alcoholism and Alcohol Abuse (NIAAA) conceives BD as drinking 70 g (men) or 56 g (women) in less than two hours. We compared the subjects delineated by each definition. Methods: Eight-center cross-sectional study among 11, 695 subjects hospitalized in emergency wards. Participants completed the Alcohol Use Disorders Identification Test – Consumption (AUDIT-C), CAGE and Rapid Alcohol Problem Screen 4 (RAPS4-QF) questionnaires. The WHO criteria were investigated using the RAPS4-QF. Independent questions assessed the NIAAA criteria. The main medical admission motive was noted. The characteristics of subjects meeting respectively: 1) the exclusive WHO criteria (BD1); 2) the NIAAA criteria (BD2); and 3) no BD criteria (noBD) were compared using multinomial regression analyses. Binary age- and gender-adjusted regression analyses directly compared BD1 and BD2. Subjects with at least four drinking occasions per week were excluded from the analyses, to withdrawn regular heavy drinking. Results: Compared to BD1, BD2 subjects were more frequently males (OR = 1.67 [1.39–2.0]), single (aOR = 1.64 [1.36–1.98]) and unemployed (aOR = 1.57 [1.27–1.90]). BD2 reported significantly more drinks per occasion, and higher heavy drinking frequencies. Previous alcohol-related remarks from family (aOR = 3.00 [2.53–3.56]), ever drinking on waking-up (aOR = 2.05 [1.37–2.72]), and admission for psychiatric motive (aOR = 2.27 [1.68–3.07]) were more frequent among BD2 subjects. Conclusions: Compared to WHO criteria, NIAAA criteria for BD delineate subjects with more concerning drinking patterns and alcohol aftermaths.